2016
DOI: 10.1002/jbm.b.33605
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of osteoinductive and endothelial differentiation potential of Platelet‐Rich Plasma incorporated Gelatin‐Nanohydroxyapatite Fibrous Matrix

Abstract: In this study, platelet-rich plasma (PRP) was incorporated into gelatin-nanohydroxyapatite fibrous scaffold in two forms (PRP gel as coating on the scaffold [PCSC] and PRP powder within the scaffold [PCSL] and investigated for (a) growth factor release; (b) stability of scaffold at different temperature; (c) stability of scaffold before and after ETO sterilization; and (d) osteogenic and endothelial differentiation potential using mesenchymal stem cells (MSCs). PCSC demonstrated a high and burst growth factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In a former study, we reported a positive effect of PRP on endothelial cells due to the released growth factors from PRP . We and others demonstrated that PRP induces homing, adhesion, cell proliferation, migration and the osteoinductive potential of osteoblasts and mesenchymal stem cells as well as the proliferation and endothelial differentiation capacity of endothelial cells …”
Section: Discussionmentioning
confidence: 86%
“…In a former study, we reported a positive effect of PRP on endothelial cells due to the released growth factors from PRP . We and others demonstrated that PRP induces homing, adhesion, cell proliferation, migration and the osteoinductive potential of osteoblasts and mesenchymal stem cells as well as the proliferation and endothelial differentiation capacity of endothelial cells …”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, gelatin-calcium phosphate nanofibers, composed of β-TCP nanoparticles incorporated into electropunk gelatin nanofibers, improved proliferation and osteogenic differentiation of rat MSCs compared to pure calcium phosphate nanofibers (Kuttappan et al, 2016). Lastly, gelatin is also an ideal carrier for proteins and various growth factors (Krishnan et al, 2015;Anjana et al, 2016). For example, Gelatin/HA fibrous scaffold with platelet-rich plasma gel was able to induce the differentiation of MSCs into an osteogenic cell line (Anjana et al, 2016).…”
Section: Gelatin: a Collagen Degradation Product For Cell Adhesion Dmentioning
confidence: 99%
“…Lastly, gelatin is also an ideal carrier for proteins and various growth factors (Krishnan et al, 2015;Anjana et al, 2016). For example, Gelatin/HA fibrous scaffold with platelet-rich plasma gel was able to induce the differentiation of MSCs into an osteogenic cell line (Anjana et al, 2016).…”
Section: Gelatin: a Collagen Degradation Product For Cell Adhesion Dmentioning
confidence: 99%